Association of IS605 and cag-PAI of Helicobacter pylori Isolated from Patients with Gastrointestinal Diseases in Taiwan - Chih-Ho Lai; Chin-Lin Perng; Keng-Hsin Lan; Hwai-Jeng Lin (Gastroenterology Research and Practice)
Background. The cag pathogenicity island (cag-PAI) is one of the most important virulent determinants of Helicobacter pylori. An insertion sequence (IS) element of cag-PAI (IS605) has been found to generate H. pylori strains with varying virulence. Aim. To evaluate the impact of IS605 and cag-PAI on H. pylori strains isolated from Taiwanese patients with severity of gastric diseases. Methods. H. pylori isolates were cultured from gastric biopsies from 99 patients with peptic ulcer, chronic gastritis, and gastric carcinoma. Six distinct, well-separated colonies were isolated from each patient and analyzed by genotyping. Results. cagA, cagE, cagM, cagT, orf10, and orf13 were found to be present in 90.0%–100.0% of the H. pylori isolates. A total deletion of cagA, cagE, cagM, cagT, orf10, and orf13 was found in 1 isolate (1.0%). The IS605 element was found to be positive in 15.2% of the isolates. The presence of IS605 was higher in H. pylori isolated from patients with gastric carcinoma (25.0%) than in patients with duodenal ulcer (6.5%) or chronic gastritis (6.3%) (P<0.001). Conclusions. The majority of the patients examined had intact cag-PAI. IS605 was present in 15.2% and was higher in H. pylori isolated from patients with gastric carcinoma than in those with peptic ulcer.